E-Consumer Behaviour: Exploring the Drivers of E-Shopping - Kamarulzaman, Y. (EuroJournals, 2011)
The study explores the behavioural aspect of e-consumers in terms of drivers in conducting e-shopping. The key objective is to identify the influences of e-shoppers purchase decision in e-shopping medium. Focus group discussions were conducted with consumers who were residing in the UK and have already had experience in shopping from the Internet. Focusing on the actual consumers' shopping experience and not their shopping intention, this approach gives more advantages in identifying consumers' drivers. The study found that most of the influences given by the respondents of using e-shopping are consistent with attributes suggested by Rogers' (1995) Diffusion of Innovation Theory. E-shoppers are becoming more price sensitive, while trust and strong brand name are gaining more attention from e-shoppers. The results explicitly clarified several key contributions and implications to marketing theory and practice.